(untitled) (Journal of Economic Research & Business Administration, 2017)
This paper analyzes the status and use of the human capital of Kazakhstan in the field of science and innovation as a competitive advantage of the economy, and the possibility of upgrading to a large extent determined by the accumulated and implemented human capital, which is one of the main factors for the accelerated innovative development of the country. Theoretical material about the importance and priority of human capital for economic development was studied. The relevance of the topic was justified by the need of formation and development of new approaches and new conditions for training and upgrading scientific and technological capacity. The education, skills and experience of people define the limits and possibilities of technological, economic and social modernization of society. The paper evaluated the existing scientific and technical capacity, the reasons of relatively low innovation activity of enterprises in Kazakhstan and suggested measures for successful innovation oriented type development. The conducted analysis of the state and the use of human capital in the field of science of the Republic of Kazakhstan shows that human capital needs to be given due attention as a factor of innovative development.